Effect Of Palasha Kshara With Palasha Ghrita In The Management Of Cervical Erosion. - Lata, Bheesham; Shukla, Seema; Kapil, Soni (International Research Journal of Ayurveda & Yoga, 2020)
Karnini Yonivyapada (Cervical Erosion) is one of the very common gynecological conditions seen in gynecology OPD’s. About 80% of women in her reproductive age group suffer from this problem. Cervical erosion is a benign condition but if left untreated may leads up to infertility. A cardinal symptom of this disease is white discharge per vaginum which is very common in women. Electric Cauterization is known treatment for cervical erosion but chances of recurrence of the disease are high. But the Ayurvedic management seems to be more practical, cost effective and showing better result with negligible side effects. Keeping this fact in mind the present clinical study has been undertaken. Material and method: Total 50 patients of cervical erosion and fulfilling the inclusion criteria were selected for this study, from Deptt. Of Stree roga and Prasuti tantra. O.P.D. Result: The total effect of drug was evaluated on the basis of signs and symptoms after completion of therapy. Overall effect of therapy shows 89.13% patients had cured and 10.86% patients had marked improvement in sign and symptoms. Group –I revealed better results than group –II over total criteria of assessment Conclusion: The therapy proved to be effective measure in the management of cervical erosion.